Kebijakan Pemerintah Dalam Mengatasi Kelangkaan Minyak Goreng Selama Pandemi Covid-19 - Aryanto, Laila Puteri; Adinda, Mita; Anggreny, Nolasita; Lestari, Regita Ayu (Universitas Ibn Khaldun Bogor, 2024)
Cooking oil has a central role in the food needs of Indonesian society, with around 90.27% of households participating in its consumption. Even though Indonesia is one of the largest palm oil producers, price fluctuations and shortages occur, affecting people's access, especially the lower middle economic groups. This research uses a qualitative descriptive method to examine the impact of the policy of lifting the Highest Retail Price (HET) for cooking oil by the Indonesian Government in March 2022. From the research results, the policy aims to provide flexibility in the price of cooking oil, overcome shortages, and encourage domestic production. The revocation of HET creates abundant supply but at high prices, affects people's purchasing power and presents the risk of cartel practices. A thorough evaluation is needed to overcome these challenges and ensure market stability and affordable prices. Keywords: Cooking oil, Highest Retail Price, Scarcity, Market, Cartel